2016
DOI: 10.1002/1873-3468.12337
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐329 suppresses osteosarcoma development by downregulating Rab10

Abstract: MiR‐329 has been proved to be a tumor suppressor gene in various malignancies, however, its role in osteosarcoma remains elusive. We found that miR‐329 is remarkably downregulated in osteosarcoma tissues and relates to advanced stages. MiR‐329 is able to inhibit osteosarcoma cell proliferation, promote apoptosis, and induce G0/G1 cell cycle arrest. In addition, miR‐329 also suppresses wound‐healing and migration ability of osteosarcoma cells and inhibits tumorigenicity in vivo. Rab10 was identified as a target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 17 publications
3
59
0
Order By: Relevance
“…Subsequently, we found that Lentivirus-mediated RAB10 knockdown markedly inhibited HCC cell proliferation in vitro , which was consistent with other study in osteosarcoma [27]. The total cell number and cell growth rate in shRAB10 lentivirus infected group were significantly decreased or slowed down compared with those in the NC lentivirus infected group.…”
Section: Discussionsupporting
confidence: 90%
“…Subsequently, we found that Lentivirus-mediated RAB10 knockdown markedly inhibited HCC cell proliferation in vitro , which was consistent with other study in osteosarcoma [27]. The total cell number and cell growth rate in shRAB10 lentivirus infected group were significantly decreased or slowed down compared with those in the NC lentivirus infected group.…”
Section: Discussionsupporting
confidence: 90%
“…Resumption expression of miR-329 decreased tumor cell invasion capacity (32). Besides, miR-329 was lowly expressed and involved in occurrence and development of gastric cancer (33), pancreatic cancer (34), non-small cell lung cancer (35) and osteosacroma (36). These findings suggested that miR-329 may be exploited as a potent therapeutic methods for the treatments of specific cancers.…”
Section: Discussionmentioning
confidence: 95%
“…The first eight of the nineteen targets, PIAS3, p27, RAB10, DBF4, DUSP14, RBPMS, PDPN and CLTC, were considered to be closely associated with cancer progression after a literature review. Among them, RAB10, a member of the RAS superfamily, might function as an oncogenic small GTPase in OS26. Kunita A, et al .…”
Section: Discussionmentioning
confidence: 99%